Pengaruh faktor gaya pengajaran guru-guru bahasa inggeris terhadap pencapaian pelajar dalam subjek bahasa inggeris di sekolah-sekolah rendah daerah Mersing, Johor - Zamri, Basumi (2020)
The Mersing primary schools' students' achievement in English language subject in the Ujian Pencapaian Sekolah Rendah (UPSR) examination from 2013 to 2017 had shown that the students had problems to master the subject. The overall achievement of the subject compared to other subjects tested had caused Mersing to record consistent declinations over the years in terms of the percentages of students who achieved the minimum passing level and the average grade as well. The situation had placed Mersing at the bottom position in the state of Johor along that period. The findings of previous studies showed that four main factors could influence students' academic achievement, namely the students, families, teachers, and the environment, each of which has its aspects. Without denying the influence of other teacher aspects, this study tried to explore analytically the most dominant and popular teachers' teaching style based on Grasha's Teacher Teaching Style Inventory (1996). Besides that, this study also tried to identify the teaching style characteristics that are the most widely used by the teachers and also wanted to investigate to what extent the teachers' teaching style can influence the achievement of students in English language subject in Mersing. This study used a questionnaire as its main instrument and involved a total of 122 respondents of English subject teachers in the 32 national schools as well as 376 student respondents who sat for the UPSR in 2017. The questionnaire data obtained were analyzed using descriptive analysis, correlation, t-test, and one-way ANOVA in line with the objectives of the study. An interview method was carried out for 16 teachers to strengthen the findings of the questionnaire on the most dominant teaching style. The findings showed an agreement among all respondents that the Personel Model's teaching style is the most dominant and popular among teachers, while the characteristics of the Facilitator's teaching style are the most practiced by teachers. The findings also proved that the teaching styles of the Personal Model, Expert, and Formal Authority have a significant relationship to the achievement of the English language. Besides, this study also showed that there are differences in the use of teaching style by teachers based on the demographic factors of teachers in terms of gender, academic qualifications, and teaching options. Also, there are differences in student achievement based on student demographic factors in terms of location of residence, parental employment, spoken language at home, and students' interest in learning English. Based on the findings, to improve student achievement in English language subject in Mersing, a conceptual model of teaching style improvement is developed and proposed to be practiced by English teachers.